Analisis Perkembangan Infrastruktur Pariwisata Di Kawasan Strategis Pariwisata Nasional (KSPN) Rupat, Kabupaten Bengkalis, Provinsi Riau - Fatmasari, Baiq Rizky; Harahap, Agustian; Navratilova, Amelya; Andjanie, Isabella; Annisa, Lintang (Syntax Corporation, 2023)
Rupat is one of the 16 main islands in Bengkalis Regency, Riau, which has extraordinary tourism potential so that it was designated as a National Tourism Strategic Area through Government Regulation Number 50 of 2011. Strategically, tourism development on Rupat Island has not shown significant growth. The main purpose of this research is to analyze the development and availability of tourism infrastructure that can describe the causes of the underdeveloped tourism sector in Rupat Island. The research method used in this study is a qualitative descriptive method using analysis based on a literature review of secondary data collected from various sources. The results of the analysis show that the tourism infrastructure on Rupat Island which includes accessibility, public infrastructure, public facilities, and tourism facilities is still inadequate to support tourism sector activities both in terms of availability and existing conditions.